Effect of Destination Image on Tourist Satisfaction and Destination Loyalty: A Study of Ecotourism Destinations in Uganda - Mbira, Charles (Journal of Hospitality and Tourism, 2024)
Purpose: The aim of the study was to assess the effect of destination image on tourist satisfaction and destination loyalty, a study of ecotourism destinations in Uganda. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study emphasized that a positive destination image significantly influences tourist satisfaction, indicating that perceptions of an ecotourism destination directly impact visitors' overall experience and contentment. Additionally, the research highlighted that tourist satisfaction is a crucial driver of destination loyalty, suggesting that when tourists are satisfied with their experience, they are more likely to return to the destination or recommend it to others. Moreover, the study underscored the importance of promoting ecotourism destinations accurately to align tourists' expectations with the reality of the experience, thereby enhancing satisfaction and loyalty. Implications to Theory, Practice and Policy: Social exchange theory, theory of planned behavior and self-determination theory may be used to anchor future studies on assessing effect of destination image on tourist satisfaction and destination loyalty, a study of ecotourism destinations in Uganda. From a practical perspective, the study offers actionable recommendations for destination management organizations (DMOs), tourism operators, and other stakeholders involved in ecotourism development. The findings have implications for policymaking aimed at promoting sustainable tourism development and conservation efforts in ecotourism destinations.